Behaviour of Oil Palm Shell (OPS) Hybrid Precast Concrete Flooring Slab under 2-Line Loading - Ng, C.H.; Ideris, Z.; Narayanan,, S.P; Mannan, M.A.; Hidayati, A.; Kurian, V.J. (7th International Congress 'Concrete: Constructon's Sustainable Option', 2008)
Worldwide, approximately half of the floors used in commercial and domestic buildings are of precast concrete which offers both design and cost advantages over traditional methods such as cast in-situ concrete, steel-concrete composite and timber floors. Construction Industry Development Board (CIDB) has taken many initiatives to industrialize the Malaysian construction industry by promoting the use of Industrialized Building System (IBS) which involve the use of prefabricated and precast concrete building components and off-site construction. The nature of the construction industry operations has high potential impact on the environment. Therefore the strategy to promote sustainable development and a green construction industry has become critical yet essential. Due to scarcity of natural resources, researchers are focusing more on developing renewable construction materials. Oil Palm Shell (OPS), about 4 millions tonnes of which are produced as solid waste annually from palm oil industry in Malaysia, is one such renewable material. The use of OPS as aggregate for manufacture of grade 30 concrete has been established at UMS through strength and durability studies on cube, cylinder and plain beam and on reinforced concrete beams of 3 m span. This study investigates the behaviour of four OPS precast concrete flooring slabs under 2-line loading. For precast slabs, due to higher strength requirements during transport and lifting, a suitable mix of OPS and granite/ sandstone, called hybrid concrete, was developed through mix design. Slabs were made of OPS concrete and OPS hybrid concrete were reinforced with either high yield steel T10 or A393 (200 x 200 mm spacing). The slabs were water-cured for 7 days and tested at 28 days. The bending moment, deflection, cracks and strain distribution of OPS hybrid precast slabs are compared with conventional slabs. The OPS hybrid concrete slabs satisfied the strength requirement as per lifting/ transporting and serviceability condition.